Digital-based thermoelectric generator. Issue 1 (1st January 2022) - Azhar; Lathifah, M F; Doyan, A; Susilawati; Hudha, L S
Abstract: A thermoelectric generator or also known as a Seebeck generator is an electrical generator device that converts temperature differences into electrical energy using a phenomenon called the Seebeck effect. To find out the magnitude of the voltage generated by the thermoelectric, a series of tests on the thermoelectric must be carried out where one of the test methods is to provide a significant temperature difference on both sides of the thermoelectric generator using hot water media for the hot side and using ice cubes for the cold side. The test results show that the developed thermoelectric generator can generate an electric voltage of 1189.31 mV.